Empowered ventures: Unravelling the motivations behind women entrepreneurs - Iklima Husna Abdul Rahim; Dzulkifli Mukhtar; Siti Salwani Abdullah; Anis Amira Ab Rahman (Global Academic Excellence, 2025)
This study explores the diverse motivations that drive women entrepreneurs to pursue business ventures. Using a qualitative research approach, semi-structured interviews were conducted with 10 women entrepreneurs from various industries to uncover the personal, financial, and social factors that influence their decision-making. The findings reveal that passion for their work, the need for financial independence, family-related responsibilities, and the desire for autonomy were key motivators behind their entrepreneurial journeys. Many participants cited passion as a core driver, with others highlighting the pursuit of higher income and the flexibility to balance caregiving duties. Additionally, entrepreneurship was seen as a means to overcome economic challenges and attain professional independence. The study concludes that understanding these multifaceted motivations is critical for developing targeted policies and support systems that foster women’s entrepreneurial success. These insights contribute to the broader discourse on women’s entrepreneurship, emphasizing the need for inclusive strategies that address the unique challenges and drivers influencing their entrepreneurial pathways.